2015
DOI: 10.1080/10643389.2014.1000761
|View full text |Cite
|
Sign up to set email alerts
|

The Characterization of Feces and Urine: A Review of the Literature to Inform Advanced Treatment Technology

Abstract: The safe disposal of human excreta is of paramount importance for the health and welfare of populations living in low income countries as well as the prevention of pollution to the surrounding environment. On-site sanitation (OSS) systems are the most numerous means of treating excreta in low income countries, these facilities aim at treating human waste at source and can provide a hygienic and affordable method of waste disposal. However, current OSS systems need improvement and require further research and d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

29
768
2
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 1,031 publications
(804 citation statements)
references
References 179 publications
29
768
2
5
Order By: Relevance
“…The addition of detergents and additives which may be chemical, microbiological and enzymatic in nature, which are used for sludge stabilization and odor reduction, as found out during the baseline survey, could have contributed to increased phosphorous content. The oxidation and hydrolysis of phosphorous produces phosphates which combine with available water producing a weak phosphoric acid hence changing the pH (Rose et al, 2015). In addition, decomposition processes occurring in the pit latrine convert the phosphorus into orthophosphates which leach out of the pit to the groundwater (Nyenje, 2014).…”
Section: Variations Of Faecal Sludge Quality Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The addition of detergents and additives which may be chemical, microbiological and enzymatic in nature, which are used for sludge stabilization and odor reduction, as found out during the baseline survey, could have contributed to increased phosphorous content. The oxidation and hydrolysis of phosphorous produces phosphates which combine with available water producing a weak phosphoric acid hence changing the pH (Rose et al, 2015). In addition, decomposition processes occurring in the pit latrine convert the phosphorus into orthophosphates which leach out of the pit to the groundwater (Nyenje, 2014).…”
Section: Variations Of Faecal Sludge Quality Propertiesmentioning
confidence: 99%
“…The 77.6% variance indicated that there was a variation within the parameters mainly because all the 55 pit latrines analyzed were used by different households living in different slums with various user habits. In addition, since their economic status is different, their diets are also different thus contributing to variation in FS properties (Rose et al, 2015;Zziwa et al, 2014;Nwaneri, 2009). The first principal component (PC1) accounted for 29.62% of the total variance and was positive and largely contributed to by moisture content (MC) and total solids (TS) and least due to Ash content (AC).…”
Section: Variations Of Faecal Sludge Quality Propertiesmentioning
confidence: 99%
“…The moisture content in human faeces is between 63 and 86 per cent w/w (Rose et al, 2015), while urine is mainly composed of water: between 93 and 96 per cent w/w (Polprasert, 1995).…”
Section: Human Faecal Sludge Characterizationmentioning
confidence: 99%
“…[18,19] Creatinine and urea were prepared in concentrations higher than expected in human urine, i.e. values higher than normal (100 mM vs. 16 mM and 0.5 M vs. 0.39 M for creatinine and urea, respectively), [14,19] and underwent the same sample preparation procedure as described for urine samples. The spectra shown in Figure 3 indicate that, in fact, urea and creatinine do not significantly interfere with spectrophotometric or spectrofluorometric determination of MDA-TBA2 adduct.…”
Section: Sample Preparation and Testing For Possible Interferencesmentioning
confidence: 99%
“…[13] Urine composition varies due to differences in individual water balance, environmental conditions, physical exercise and nutrition [14] and the standard addition method provides reasonable means to account for possible matrix interference effects, i.e. recovery.…”
Section: Sample Collection and Preparationmentioning
confidence: 99%